ANALISIS KESULITAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL HOTS MATA PELAJARAN EKONOMI KELAS XI IPS - Halifah, Syarifah; Asriati, Nuraini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was conducted at SMA Negeri 11 Pontianak, with six research informants one economics teacher in class XI IPS and five students in class XI IPS 2 who experienced difficulties in solving economic HOTS questions which aims to find out the types of difficulties faced by students in solving economic HOTS questions. In this research, the method used is a qualitative case study, and the data collected through tests and interviews. The data analysis process was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the difficulty of students in solving HOTS questions in economic subjects on national income material was divided into 4 difficulties based on Polya's stages (1) Difficulty understanding the problem, the difficulty lies in the lack of ability for students as a whole understand the problem and could not write the steps needed to solve the question. (2) Difficulty making the solution plan, Trouble lies with the inability of students to include the formula used problems and they incorrectly applied the equation used to solve problems. (3) Difficulty implementing the plan, the difficulty lies in the lack of understanding of the concept in understanding the steps of solving any problems and less understanding of the question.